Effect of cooking and storage temperature on resistant starch in commonly consumed Indian wheat products and its effect upon blood glucose level - Kaur, Prabhjot; Kaur, Harpreet; Aggarwal, Renuka; Bains, Kiran; Mahal, Amrit Kaur; Gupta, O. P; Singla, Lachhman Das; Singh, Kulvinder (Frontiers in Nutrition, 2023)
Background/objectives The health benefits provided by resistant starch have been well documented; however, few studies are available on the resistant starch content of wheat products in India. Moreover, few studies have examined the in vivo efficacy of resistant starch in wheat products in improving glucose levels. This study was conducted to evaluate the effect of cooking and storage temperature on the formation of resistant starch in Indian wheat products and its effect on blood glucose levels in humans and rats. Methods Wheat products were prepared by common cooking methods including roasting (Chapati), boiling (Dalia), Shallow frying (Paratha), and Deep frying (Poori). They were then stored at different temperatures including freshly prepared within 1 h (T1), stored for 24 h at room temperature (20-22°C) (T2), kept at 4°C for 24 h (T3) and reheated after storing at 4°C for 24 h (T4). The products were then analyzed for proximate composition (moisture, crude protein, crude fat, ash crude fibre, and carbohydrates). The effect of different cooking methods and storage temperatures on Resistant, non-resistant and total starch, total dietary fibre (soluble and insoluble), in vitro starch digestion rate (rapidly and slowly digestible starch), amylose and amylopectin content were analysed using standard operating procedures. The effect of products found to have higher resistant starch was studied on the post prandial blood glucose response of 10 healthy individuals using change in by analysing their glycemic index and glycemic load of wheat products. Further, the effect of resistant starch rich chapati on the blood glucose level of rats was also studied. Tukey’s test in factorial CRD was used to assess the effect of cooking and temperature on various parameters. Results The amount of resistant starch was found to be high in dalia (boiling, 7.74%), followed by parantha (shallow frying, 4.94%), chapati (roasting, 2.77%) and poori (deep frying 2.47%). Under different storage temperatures, it was found high in products stored at 4°C (T3), followed by products stored at room temperature (T2), reheated products (T4) and lesser in freshly prepared products (T1). The glycemic index and glycemic load were found low in chapati (43, 32.3) and dalia (41.1, 28.6) stored at 4°C (T3) compared to others. The resistant starch content found in chapati stored at T3 was found to be more effective at reducing blood glucose levels in rats from 291.0 mg/100 mL to 225.2 mg/100 mL in 28 days of study compared to freshly prepared chapati (T1) and stored at room temperature (T2). Conclusion Cooking methods including boiling, roasting and shallow frying increased the amount of resistant starch in foods, but cooking methods such as deep frying decreased the amount of resistant starch in food. Products stored at 4°C and at room temperature for 24 h increased the amount of resistant starch whereas the products that were freshly cooked and reheated decreased the amount of resistant starch in foods. At 4°C the stored products have a high amount of insoluble dietary fibre, slowly digestible starch, high amylose and low glycemic index. They take time to digest, meaning that they slowly increase blood glucose levels. The effect of insoluble dietary fibre and resistant starch in the inhibition of glucose diffusion in the small intestine is suggested to be due to the absorption or inclusion of the smaller sugar molecules. In vivo research showed that fibre and resistant starch in the digestive system of rats acts as the main factors in slowing glucose absorption and reducing a rise in blood glucose levels by promoting glycogen synthesis and inhibition of gluconeogenesis.